PENGARUH FISCAL STRESS DAN LEGISLATURE SIZE TERHADAP EXPENDITURE CHANGE PADA KABUPATEN/KOTA DI SUMATERA UTARA - Afrah Junita; Syukriy Abdullah (Jurnal Akuntansi, 2016)
The purpose of this study was to examine the effect of fiscal pressure (fiscal stress) and the size of the legislature (Legislature size) to change the budget at the district and city in North Sumatra. Results obtained from the model predictions showed that statistically, fiscal pressures negatively affect regional budget changes, while the magnitude of the effect is the opposite legislature. These results suggest that changes in the budget is very important in responding to the magnitude of the reception and the number of board members reflect the interests that must be accommodated in the adjustment state budget.